Development of an information literacy education model based on school culture mediated by motivation and self-efficacy / Chua Lee Lee - Chua , Lee Lee (2018)
The purpose of this study was to develop an Information Literacy Education (ILE) model based on school information literacy culture created through hidden curriculum and mediated by motivation and self-efficacy. This model plays as a supporting system to support current ILE efforts with the hope to minimize the current problems of ILE faced in Malaysian schools. By utilizing the Design and Developmental Research approach (Richey & Klein, 2007), this study was conducted in three phases. Phase 1 was needs analysis phase. This phase was a mixed method research design and consisted of two stages. Stage one was a focus group discussion with school administrators. Three themes were identified from the qualitative data, they were school culture that values: (i) Information and Communication Technology (ICT) and student-centered teaching and learning, (ii) independent learning and autonomy support, and (iii) character development. Stage two was a survey involving 386 secondary school teachers. The needs analysis phase justified the need to develop the ILE model. Next, the model was then developed at Phase 2, the model development phase. The development process of the model was guided by Social Cognitive Theory and Self-Determination Theory. This phase also consisted of two stages. Stage one was the instruments development and validation. Stage two was the hypotheses development and hypothesized model development. The data were collected from 610 secondary school students. Through these processes, a hypothesized ILE model was developed. This model contained of four main constructs: The School Information Literacy Culture consisted of four factors, namely Perceived Autonomy Support, Fairness, Respect, and Activities; the Information Literacy Skills was defined as Information literacy, Independent Learning, Mutual Respect and Ethics; Motivation was operationalized through Introjected Regulation and Identified Regulation; and Self-efficacy was measured by a single factor with six items. Finally, the hypothesized model of ILE was evaluated using Partial Least Square Structural Equation Modeling (PLS-SEM) approach in Phase 3, the model evaluation phase. This phase took a three-stage approach where Stage one was model specification, Stage two was the evaluation of measurement model and Stage three was the evaluation of structural model. The measurement model was assessed on internal consistency reliability, indicator reliability, convergent validity and discriminant validity in two levels. The first level was the first-order constructs and second level were the higher-level constructs. The results of analysis indicated that both levels of measurement models fit the data properly. The hypothesized structural model was examined in the second stage including six direct paths representing hypotheses H1, H2, H3, H4, H5 and H6 and three indirect paths representing hypotheses H7, H8 and H9. The empirical findings indicated that all of the hypotheses were supported. Through the rigorous model development and the confirmed reliability and validity of the model evaluation, the ILE model meets the requirement of its role as a supporting system to support current ILE efforts by embedding the information literacy learning into school culture and also focusing on its influence on students’ motivation and self-efficacy to enhance students’ information literacy skills.